2019
DOI: 10.1002/jssc.201900307
|View full text |Cite
|
Sign up to set email alerts
|

Epoxide‐derived mixed‐mode chromatographic stationary phases for separation of active substances in fixed‐dose combination drugs

Abstract: A method for the preparation of novel mixed‐mode reversed‐phase/strong cation exchange stationary phase for the separation of fixed‐dose combination drugs has been developed. An epoxysilane bonded silica prepared by vapor phase deposition was used as a starting material to produce diol, octadecyl, sulfonate, and mixed octadecyl/sulfonate groups bonded silica phases. The chemical structure and surface coverage of the functional groups on these synthesized phases were confirmed by fourier‐transform infrared and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The different organic compounds [9–11], such as acridine derivatives [12], ethylene‐bridged hybrid C18 [13], imidazolium derivatives [14–16], benzimidazole [17], 2‐methylindole [18], quinolinium [19], epoxide‐derived [20], calix[4]arene‐derivatives [21, 22], tetra‐proline‐modified calix[4]arene [23], types of biomolecules [24], and amide and amine groups [25–27], can be bonded on silica surface to design MM stationary phases. Moreover, to improve the retention, many polar groups have been embedded on the alkyl hydrocarbon chain of stationary phases, such as amide [28–31], carbamate [32], ether, ammonium [33], urea [34], and poly(ionic liquid) [35].…”
Section: Introductionmentioning
confidence: 99%
“…The different organic compounds [9–11], such as acridine derivatives [12], ethylene‐bridged hybrid C18 [13], imidazolium derivatives [14–16], benzimidazole [17], 2‐methylindole [18], quinolinium [19], epoxide‐derived [20], calix[4]arene‐derivatives [21, 22], tetra‐proline‐modified calix[4]arene [23], types of biomolecules [24], and amide and amine groups [25–27], can be bonded on silica surface to design MM stationary phases. Moreover, to improve the retention, many polar groups have been embedded on the alkyl hydrocarbon chain of stationary phases, such as amide [28–31], carbamate [32], ether, ammonium [33], urea [34], and poly(ionic liquid) [35].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional liquid chromatography uses a monofunctional stationary phase such as reversed phase or ion exchanger to separate the mixture, and the solute retention is primarily controlled by a single mode of action based on hydrophobic or ionic interactions. In contrast, mixed-mode chromatography uses a multifunctional stationary phase to achieve separation by multivalent complexation between a multivalent compound and a multivalent stationary phase. , Recently, we reported studies of the retention behavior of divalent solutes (such as alkylanilines and alkylbenzoic acids) in mixed-mode chromatography and demonstrated that solute retention is highly dependent on the cooperative binding due to a combination of hydrophobic and ionic interactions. , Liquid chromatography can be used not only as a separation method for a range of compounds but also as a means of characterizing noncovalent interactions in porous materials. In the latter application, the porous material to be investigated is loaded into a chromatographic column and equilibrated with a mobile phase.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Recently, we reported studies of the retention behavior of divalent solutes (such as alkylanilines and alkylbenzoic acids) in mixed-mode chromatography and demonstrated that solute retention is highly dependent on the cooperative binding due to a combination of hydrophobic and ionic interactions. 27,28 Liquid chromatography can be used not only as a separation method for a range of compounds but also as a means of characterizing noncovalent interactions in porous materials. In the latter application, the porous material to be investigated is loaded into a chromatographic column and equilibrated with a mobile phase.…”
Section: ■ Introductionmentioning
confidence: 99%